The Importance Of Knowledge Of Post Partum Mothers In Getting Optimal Breast Milk In Makassar City Maternity Hospital, South Sulawesi - Asmirah, Rika; Srifitayani, Nur Rahma; Mudrika, Mudrika; Herlina, Herlina; Haruna, Sri Rahma; Asmin, Risna Yunita; Rohmi, Rohmi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Oxytocin massage is also a solution to overcome irregular breast milk production. This massage is performed along the spine to stimulate the hormones prolactin and oxytocin after giving birth. The purpose of this study was to determine the role, benefits and functions of the combination of breast care and oxytocin massage on breast milk production in postpartum mothers and to facilitate breast milk production. The research method was quasi-experimental, with a posttest-only control design. Using consecutive sampling techniques. Interventions were given from the first day to the third day postpartum, then observations were carried out. Data normality test using the Shapiro-Wilk test, data analysis using the independent t-test. The research results obtained a significance value with the average number of the combination group and the control group. The conclusion of this study is that the combination of breast care and oxytocin massage is effective in breast milk production in postpartum mothers. When massaging the spine, it can cause a neurogenic reflex that speeds up the work of the parasympathetic nerves to convey commands to the back of the brain. As a result of the stimulatory signal, the potential action process of oxytocin is released into the systemic blood from the posterior pituitary. In the bloodstream, oxytocin is delivered to the myoepithelial cells of the alveoli and uterus so that oxytocin will stimulate these cells which cause the alveolar sacs to be compressed and the ducts to shorten and widen.